Potential Field Data Guided Seismic Forward Modelling of Basement Structures: a Case Study from Offshore Nile Delta Basin - Hanafy, S.; Mehmoud, Sharaf Elden; Nimmagadda, Shastri L. (2016)
The offshore Nile Delta region has huge exploration potential, keeping in view the existing commercial oil and gas fields in and around this basin. The majority of the offshore Nile Delta basin is underexplored. Sparsity of geophysical data coverage and ambiguity in the interpretation of existing geophysical data have held back the exploration for many decades. In order to assess and evaluate the exploration potential, it is important to estimate the depth to the basement, the nature of basement and its topography. Identifying the basement reflector based on the current seismic data is challenging, because of limitations of the resolution and record length of the seismic data. Moreover, an estimation of sedimentary column is paramount for further detailed geological and geophysical investigations. The objective of the research is to perform seismic forward modelling of the basement reflector, guided by gravity and magnetic field data, and minimize the ambiguity involved in a single geophysical method of interpretation. The geophysical properties and their contrasts derived from seismic, gravity and magnetic methods of exploration are various criteria used in the integration and modelling process. Seismic stacking velocity data and depth values interpreted from gravity and magnetic field data are used in the modelling process. The uncertainty in modelling the basement character is assessed based on the stacking velocities and seismo-geological cross-sections interpreted from 2D seismic data, instead of cross-sections obtained from unreliable seismically derived depth data. The analysis of errors observed in the seismic data due to younger layer-cake reflections interfering with the basement reflector are analysed and the observed errors in the velocity models are accordingly reconciled based on the potential field data. The potential field data interpretation guiding the seismic forward modelling facilitates the redesign process of seismic data acquisition and processing in the hugely unexplored offshore Nile Delta basin in Egypt.